2017
DOI: 10.3233/thc-171301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed electromagnetic fields on histomorphometry and osteocalcin in disuse osteoporosis rats

Abstract: Abstract. OBJECTIVE: Bone histomorphometry and the concentration of the serum osteocalcin expression were observed in disuse osteoporosis (DOP) rats in order to explore the mechanism of pulsed electromagnetic fields in treating DOP. METHODS: Female SD rats, weighing 250 ∼ 280 g, were randomly divided into 4 groups: a control group and three experimental groups. The right hindlimbs of all the rats were immobilized by tibia-tail fixation, except for those in the INT group. The ALN group rats were given an alendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, this assumption requires further investigation. Examples are the studies of Cai et al [82], Li et al [83], or Jing et al [84], which investigated the effect of ELF-PEMF on architecture and mechanical properties of bone in diabetic animals, known to have skeletal deficiencies, or the studies of Lei et al [74,85], Li et al [86], Zhou et al [87,88], or Androjna et al [89], which investigated the effect of ELF-PEMF on bone quality in osteoporotic animals.…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 99%
“…However, this assumption requires further investigation. Examples are the studies of Cai et al [82], Li et al [83], or Jing et al [84], which investigated the effect of ELF-PEMF on architecture and mechanical properties of bone in diabetic animals, known to have skeletal deficiencies, or the studies of Lei et al [74,85], Li et al [86], Zhou et al [87,88], or Androjna et al [89], which investigated the effect of ELF-PEMF on bone quality in osteoporotic animals.…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 99%
“…Electromagnetic fields (EMFs) of extremely low frequency have been considered to be a promising therapy for a wide range of bone diseases, such as fresh and nonunion fractures, osteoarthritis, and osteoporosis (Funk, Monsees, & Özkucur, ). Accumulating evidence has shown that EMFs promote osteogenic differentiation and mineralization of bone marrow stromal cells (BMSCs) and osteoblasts, inhibit osteoclast formation and its bone resorption activity, and prevent bone loss in animal models of disuse and ovariectomy‐induced osteoporosis (Barnaba et al, ; Chang, Chang, Tsai, & Shih, ; Chang, Chang, Wu, & Shih, ; Jing et al, , ; He, Selvamurugan, Warshaw, & Partridge, ; Hong, Kang, Yi, Kim, & Cho, ; Li et al, ; Ongaro et al, ; Schwartz et al, ; Tong et al, ; Xie et al, ; Yan et al, ; J. Zhang et al, ; Zhou et al, ). Clinical investigations further confirmed that EMFs increased bone mineral density (BMD) and prevented bone loss in the patients with osteoporosis (Garland, Adkins, Matsuno, & Stewart, ; Tabrah, Ross, Hoffmeier, & Gilbert, ).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of PEMF used in 20 studies ranged from 0.1 to 3.82 mT, with three studies using the intensity of 80 µA/cm 2 , 30 mW/cm 2 , and 1-2 mV/cm, respectively [Chang and Chang, 2003;Lirani-Galvão et al, 2006;Behari, 2008], and PEMF intensity used by one article was 1 T [Lin et al, 2020]. Eighteen articles provided details of the time of PEMF initiation, varying from the day after OVX to 12 weeks after the operation; six articles did not provide any information on the time of PEMF initiation [Jing et al, 2013;Zhou et al, 2013;Li et al, 2017aLi et al, , 2018Lei et al, 2018].…”
Section: Characteristics Of Animals and Groupsmentioning
confidence: 99%